2016
DOI: 10.18632/oncotarget.8015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and consequences of heterogeneity in the circulating tumor cell compartment

Abstract: A growing understanding of the molecular biology of cancer and the identification of specific aberrations driving cancer evolution have led to the development of various targeted agents. Therapeutic decisions concerning these drugs are often guided by single biopsies of the primary tumor. Yet, it is well known that tumors can exhibit significant heterogeneity and change over time as a result of selective pressure. Circulating tumor cells (CTCs) are shed from various tumor sites and are thought to represent the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 149 publications
(214 reference statements)
3
50
0
Order By: Relevance
“…The broad heterogeneity of CTCs in the blood of cancer patients, including ovarian cancer, has already been indicated by several independent reports [2527]. We may hypothesize that ERCC1-expressing CTCs play a dominant role during the course of the disease, which is corroborated by the fact that the rate of exclusively ERCC1-positive CTCs did not decrease after platinum-based chemotherapy.…”
Section: Discussionsupporting
confidence: 67%
“…The broad heterogeneity of CTCs in the blood of cancer patients, including ovarian cancer, has already been indicated by several independent reports [2527]. We may hypothesize that ERCC1-expressing CTCs play a dominant role during the course of the disease, which is corroborated by the fact that the rate of exclusively ERCC1-positive CTCs did not decrease after platinum-based chemotherapy.…”
Section: Discussionsupporting
confidence: 67%
“…Single-cell analyses have revealed that CTCs often comprise a heterogeneous population of cells. Logically, this heterogeneity may reflect the extent of intratumor heterogeneity (ITH) [65][66][67][68][69][70] and may have important implications for prognosis and resistance to therapy. Indeed, a recent study of archived samples from patients with metastatic breast cancer found 85% concordance between CTCs and metastatic sites in terms of mutations and copy-number profile [71].…”
Section: Ctc Heterogeneitymentioning
confidence: 99%
“…In addition there are a variety of NGS platforms available including second generation, sequencing of an ensemble of DNA molecules with wash-and-scan techniques and third generation, sequencing single DNA molecules without the need to halt between read steps, whether enzymatic or otherwise 145 (Table 3) 136,[146][147][148][149][150][151][152][153][154][155][156][157][158][159][160] .…”
Section: Ctc Molecular Profilingmentioning
confidence: 99%